Partnership between Secondary Schools and Community Agencies to Improve the Outcomes of Students with Intellectual Disabilities (Reality and Development) (Journal Of Educational and Psychological Researches, 2023)
AbstractThe current research aims to identify the level of partnership between school and community agencies to improve secondary school outcomes for students with intellectual disabilities and develop strategies that help enhance community partnerships between schools and agencies. The researcher used the qualitative research approach; he utilized the interviews as a tool for data collection. The sample of research included (12) participants: three female school leaders, three male-school leaders, three female-school supervisors, and three male-school supervisors in schools that have programs for students with intellectual disabilities in Riyadh. The results of the study showed that the level of partnership between schools and community agencies ranges from medium to weak. The companies' response to the community partnership between them and schools ranged also from medium to weak. There was a discrepancy in the number of partnerships and the number of students benefiting from them. There is a high awareness among leaders and supervisors about the benefits of the partnerships. Partnerships are often led by leaders, supervisors, and special education teachers. The partnership benefits students in many ways, such as helping them to engage in society, providing income for them and empowering active persons in the community, and linking them to various community agencies.